Dislocations in Magnetite: Experimental Observations of their Structural, Magnetic, and Low-temperature Effects - Lindquist, Anna K. (My University, 2013)
Magnetite (Fe3O4) is the most important mineral to the rock magnetic and paleomagnetic communities and is ubiquitous in igneous, sedimentary, and metamorphic rocks. Larger multidomain (MD) magnetite grains are more common than single domain grains, so understanding how they record paleomagnetic fields would be a boon to paleomagnetists. MD magnetite grains are divided into multiple domains, regions with uniform magnetization, separated by domain walls. Domain walls sweep through magnetite grains easily, so slight changes in ambient magnetic fields can alter the magnetization of MD magnetite. Because of this, MD magnetite is not considered reliable for paleomagnetic studies, and the mechanisms by which MD grains may record past magnetic fields are not well understood. Dislocations, linear crystallographic defects, may increase magnetic coercivity by pinning domain walls in place. This study, for the first time, experimentally investigates this pinning behavior by using a transmission electron microscope (TEM) to simultaneously image magnetic domain walls, dislocations, and low-temperature twin structures. Magnetite grains were deformed in the dislocation glide regime, which is active in natural magnetite grains. Dislocations were not uniformly distributed throughout the sample, but regions with more and longer dislocations pinned domain walls more strongly. First-order reversal curve diagrams demonstrate the presence of regions with pinning strengths of over 125 mT. The strength of domain wall pinning at dislocations was found experimentally and theoretically to be proportional to dislocation length, with longer dislocations pinning more strongly. Average pinning fields were around 0.2 mT. Magnetite grains with more uniformly distributed dislocations would likely have coercivities that were high enough to enable MD magnetite to record geomagnetic fields over geologic timescales. Further, low-temperature TEM and magnetic studies demonstrated that dislocations can affect twin growth in magnetite below the Verwey transition. Deformed magnetite samples had more soft-shouldered Verwey transitions and were able to retain more remanence after low-temperature demagnetization (LTD). Therefore, MD magnetite grains may be able to retain relevant magnetizations, even after LTD. Dislocation length, density, and distribution are then all important considerations when investigating the ways in which MD magnetite may retain a stable record of paleomagnetic field characteristics, even after LTD.
University of Minnesota Ph.D. dissertation. September 2013. Major: Geophysics. Advisor: Joshua M. Feinberg. 4 computer files (1 PDF; xi, 93 pages) + 3 MPEG-4 video files.
Keywords: Geophysics; Dislocation; Domain wall; Magnetite; Multidomain; Transmission electron microscopy; Verwey